Confronting 'race' and policy: 'how can you research something you say does not exist?'. Issue 2 (3rd May 2016) - Hylton, Kevin; Long, Jonathan
CONTEXT: This section of the journal encourages discussion between several authors on a policy-related topic. The same question may, therefore, be addressed from different theoretical, cultural or spatial perspectives. Dialogues may be applied or highly abstract. This Dialogue starts with this contribution and is followed by three comments by Herman Ouseleydoi.org/10.1080/19407963.2015.1115951 ; Daryl Adairdoi.org/10.1080/19407963.2015.1115952 and, finally, Jacco van Sterkenburg's reflections prompted by the observations of fellow contributorsdoi.org/10.1080/19407963.2015.1115953 .